2020
DOI: 10.3390/jpm10040170
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of MiR-22 Fosters Diet-Induced Obesity and NAFLD Development

Abstract: miR-22 is one of the most abundant miRNAs in the liver and alterations of its hepatic expression have been associated with the development of hepatic steatosis and insulin resistance, as well as cancer. However, the pathophysiological roles of miR-22-3p in the deregulated hepatic metabolism with obesity and cancer remains poorly characterized. Herein, we observed that alterations of hepatic miR-22-3p expression with non-alcoholic fatty liver disease (NAFLD) in the context of obesity are not consistent in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…The long noncoding RNA MIAT is increased in a rat model of diabetic cardiomyopathy and HG-cultured neonatal cardiomyocytes, which upregulates death-associated protein kinase 2 expression by sponging miR-22-3p and consequently leads to cardiomyocyte apoptosis [28]. Moreover, Mir22-knockout mice present dramatically exacerbated fat mass gain, hepatomegaly, and a liver steatosis response to high-fat diet feeding compared to control mice [49]. Although miR-22-3p has been demonstrated to be a master regulator of lipid and glucose metabolism with differential effects on specific organs, its roles in the physiological and pathological processes of the salivary gland remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The long noncoding RNA MIAT is increased in a rat model of diabetic cardiomyopathy and HG-cultured neonatal cardiomyocytes, which upregulates death-associated protein kinase 2 expression by sponging miR-22-3p and consequently leads to cardiomyocyte apoptosis [28]. Moreover, Mir22-knockout mice present dramatically exacerbated fat mass gain, hepatomegaly, and a liver steatosis response to high-fat diet feeding compared to control mice [49]. Although miR-22-3p has been demonstrated to be a master regulator of lipid and glucose metabolism with differential effects on specific organs, its roles in the physiological and pathological processes of the salivary gland remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…miR-22 is relatively abundant in cells and its overexpression may be difficult compared with those with lower expression levels such as miR-199a [ 20 , 28 30 ]. Since the length of pri-miRNA may affect miRNA expression and rAAV has a limited packaging capacity [ 25 , 26 , 31 ], it was necessary to identify the appropriate length of the pri-miR-22.…”
Section: Resultsmentioning
confidence: 99%
“…The function of miR-22 on insulin sensitivity were controversial [ 16 , 18 – 20 ]. To address this question, we investigated whether miR-22 overexpression affected bodyweight and insulin sensitivity in obese and diabetic mice induced by a high-fat diet (HFD).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this data, miR-22 was down-regulated in liver samples from patients with liver fibrosis or cirrhosis [ 81 ]. Also, Gjorgjieva and her co-workers have found that deficiency of miR-22 dramatically aggravated fat mass accumulation, hepatomegaly, and liver steatosis in mice [ 82 ]. The computational analysis suggested TGFβR1 as a potential target of miR-22 which was confirmed in the present study by the marked up-regulation of TGFβR1 in CCl 4 -rats (about 5.5- Fold) and the strong negative correlation between the hepatic expression of miR-22 and TGFβR1 mRNA.…”
Section: Discussionmentioning
confidence: 99%